A Peptide-Fc Opsonin with Pan-Amyloid Reactivity - Foster, James S.; Williams, Angela D.; Macy, Sallie; Richey, Tina; Stuckey, Alan; Wooliver, Daniel Craig; Koul-Tiwari, Richa; Martin, Emily B.; Kennel, Stephen J.; Wall, Jonathan S. (Frontiers in Immunology, 2017)
There is a continuing need for therapeutic interventions for patients with the protein misfolding disorders that result in systemic amyloidosis. Recently, specific antibodies have been employed to treat AL amyloidosis by opsonizing tissue amyloid deposits thereby inducing cell-mediated dissolution and organ improvement. To develop a pan-amyloid therapeutic agent, we have produced an Fc fusion product incorporating a peptide, p5, which binds many if not all forms of amyloid. This protein, designated Fcp5, expressed in mammalian cells, forms the desired bivalent dimer structure and retains pan-amyloid reactivity similar to the p5 peptide as measured by immunosorbent assays, immunohistochemistry, surface plasmon resonance and pulldown assays using radioiodinated Fcp5. Additionally, Fcp5 was capable of opsonizing amyloid fibrils in vitro using a pH sensitive fluorescence assay of phagocytosis. In mice, 125I-labeled Fcp5 exhibited an extended serum circulation time, relative to the p5 peptide. It specifically bound AA amyloid deposits in diseased mice, as evidenced by biodistribution and micro-autoradiographic methods, which coincided with an increase in active, Iba-1 positive macrophages in the liver at 48 h post injection of Fcp5. In healthy mice, no specific tissue accumulation was observed. The data indicate that polybasic, pan-amyloid targeting peptides, in the context of an Fc fusion, can yield amyloid reactive, opsonizing reagents that may serve as next-generation immunotherapeutics.